PENGARUH PROPILENGLIKOL TERHADAP FORMULASI DAN KARAKTERISTIK FISIK SEDIAAN PATCH EKSTRAK ETANOL DAUN INGGU (Ruta angustifolia L. Pers) - Hikma, Nurul; Yassir, Budiman; Khairi, Nur; Marwati, Marwati; Pattinggi, Patricia (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
Ruta angustifolia L.Pers contain essential oil, steroids, flavonoids, tannins, quinones, and saponins compounds which have the potential to act as analgesics. This research aimed to determine the effect of varying propylene glycol concentrations on the physical characteristics of patches using the solvent evaporation method. Patch preparations were made in 3 formulas with variations of propylene glycol, namely F1 (without propylene glycol), F2 (10%), F3 (20%), and F3 (30%), and the patch was evaluated. The results of the physical characteristics obtained were patches with a yellowish green color, typical extract smell, round shape, thin film, smooth, dry, and elastic with a folding resistance of >200 times, thickness ranging from 0.02-0.03 mm, weight uniformity meeting the requirements, namely CV value 5%, %drying loss <9.20%, humidity of each formula <9.79% with a pH of around 7. Thus, it can be concluded that the ethanol extract of inggu leaves influences the uniformity of the weight and thickness of the patch.